2003
DOI: 10.1530/eje.0.1490111
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of ghrelin in human fetuses

Abstract: Objective: Ghrelin is a GH secretagog isolated recently from rat stomach and involved in the stimulation of food intake and adiposity in rodents and humans. Moreover, subsequent studies showed that ghrelin is expressed in rat and human placenta, suggesting a possible influence of the peptide on fetal growth. The aim of this study was to evaluate circulating levels of ghrelin in appropriate for gestational age (AGA) or intrauterine growth-restricted (IUGR) fetuses. Subjects and methods: Ghrelin levels between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
1
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 31 publications
6
63
1
5
Order By: Relevance
“…As was the case in the rat, ghrelin expression has been also detected in human placenta (Gualillo et al 2001), and ghrelin has been demonstrated in human fetal circulation (Cortelazzi et al 2003). However, the role, if any, of placental and fetal ghrelin in the regulation of gestational growth and metabolism remains to be fully elucidated.…”
Section: Human Datamentioning
confidence: 94%
“…As was the case in the rat, ghrelin expression has been also detected in human placenta (Gualillo et al 2001), and ghrelin has been demonstrated in human fetal circulation (Cortelazzi et al 2003). However, the role, if any, of placental and fetal ghrelin in the regulation of gestational growth and metabolism remains to be fully elucidated.…”
Section: Human Datamentioning
confidence: 94%
“…Also since the ghrelinexpressing cells are located in the mucosa, we assessed GOAT mRNA levels in samples extracted from this source. Furthermore, taking into consideration that ghrelin mRNA levels can be influenced by the age of the animals (Gualillo et al 2001, Cortelazzi et al 2003, we first assessed GOAT mRNA levels in samples from male rats of different ages. We found that GOAT mRNA levels were relatively stable at all the ages studied (Fig.…”
Section: Goat Mrna Levels In Rat Stomachmentioning
confidence: 99%
“…Human ghrelin (hunger hormone) is a novel peptide hormone, which is predominantly synthesized in the stomach (10,12,13), but it is also synthesized in several other tissues including the central nervous system, kidney, heart, parathyroid glands, the small and large intestines, a-cells of the pancreatic islet (14), placenta (15), and salivary gland (16). It sti mulates growth hormone (GH) secretion and acts as a signal for the regulation of food intake, energy expenditure and fat accumulation, and body weight gain (12,17).…”
Section: Introductionmentioning
confidence: 99%